Intermittent negative pressure ventilation in the treatment of hypoxic hypercapnic coma in chronic respiratory insufficiency. Issue 11 (November 1996) - Corrado, A; De Paola, E; Gorini, M; Messori, A; Bruscoli, G; Nutini, S; Tozzi, D; Ginanni, R
Abstract : BACKGROUND: In recent years non-invasive ventilatory techniques have been used successfully in the treatment of acute on chronic respiratory failure (ACRF), but careful selection of patients is essential and a comatose state may represent an exclusion criterion. The aim of this retrospective and uncontrolled study was to evaluate whether a non-invasive ventilatory technique such as the iron lung could also be used successfully in patients with hypoxic hypercapnic coma, thus widening the range for application of non-invasive ventilatory techniques. METHODS: A series of 150 consecutive patients with ACRF and hypoxic hypercapnic coma admitted to our respiratory intensive care unit were evaluated retrospectively. The most common underlying condition was chronic obstructive pulmonary disease (79%). On admission a severe hypoxaemia (Pao2 5.81 (3.01) kPa) and hypercapnia (Paco2 14.88 (2.78) kPa) associated with a decompensated acidosis (pH 7.13 (0.13)) were present, the Glasgow coma score ranged from 3 to 8, and the mean APACHE II score was 31.6 (5.3). All patients underwent intermittent negative pressure ventilation with the iron lung. The study end point was based on a dichotomous classification of treatment failure (defined as death or need for endotracheal intubation) versus therapeutic success. RESULTS: There were 45 treatment failures (30%) and 36 deaths (24%). Nine patients (6%) required intubation because of lack of airway control. The median total duration of ventilation was 27 hours per patient (range 2-274). The 105 successfully treated cases recovered consciousness after a median of four hours (range 1-90) of continuous ventilatory treatment and were discharged after 12.1 (9.0) days. CONCLUSIONS: These results show that, in patients with acute on chronic respiratory failure and hypoxic hypercapnic coma, the iron lung resulted in a high rate of success. As this study has the typical limitations of all retrospective and uncontrolled studies, the results need to be formally confirmed by controlled prospective studies. Confirmation of these results could widen the range of application of non-invasive ventilatory techniques.